THE EFFECT OF DIGITAL LEARNING ON HIGH SCHOOL STUDENTS' MOTIVATION AND SATISFACTION IN THE DIGITAL ERA AND THE COVID-19 PANDEMIC - Agus Purwanto; Tawar Tawar (UJoST- Universal Journal of Science and Technology, 2024)
The purpose of this study was to analyze the effect of digital learning on motivation and the effect of digital learning on student learning satisfaction during the Covid 19 Pandemic in high schools.This research is using a quantitative research approach. In this case, this research is to determine the effect of digital learning during the pandemic period on learning motivation through high school student learning satisfaction. This study aims to describe and explain and analyze the influence of 3 (three) variables, namely the Digital Learning variable (Y), the Learning Motivation variable (X1), and the Learning Satisfaction variable (X2). The three variables above will simultaneously be tested for the relationship and the level of the relationship in this research. The exogenous variable in this study is Digital Learning (Y), while the endogenous variables are Learning Motivation (X1) and Learning Satisfaction (X2). The strength level of the relationship between exogenous variables and endogenous variables was analyzed to determine the predictive ability of exogenous variables to endogenous variables and to determine the construct model of variables that have a significant relationship, the data analysis technique used was structural equation modeling (SEM) with SmartPLS 3.0 software tools. The respondents to this study were 450 high school teachers who were determined using the simple random sampling method. The questionnaire was designed using a Liker scale of 7, the questionnaires were distributed online using social media. The results of the analysis show that digital learning has a significant effect on the learning motivation variable, the use of digital technology as a Learning facilities have a positive effect on the emergence of student learning motivation so that it is expected that student learning achievement can be achieved optimally. Digital learning has a significant effect on learning satisfaction variables. With Digital Learning, some students are not influenced by the environment, students maximally learn by their own will (for example, independent learning, with varied places and media) even without motivation or reinforcement from people around them, work regularly and focus and like competition. Appropriate use of new technology can assist in delivering material in a way that students can learn successfully and find satisfaction.